Acoustic-based detection of debonding in thin-layer semi-rigid base asphalt pavements using a-weighted sound pressure levels - Changfeng Hao; Min Ye; Qing Zhang; Zhongyu Li; Xianbao Zuo; Zhen Sun (PLoS ONE, 2025)
Thin-layer interlayer debonding in semi-rigid base asphalt pavements is difficult to detect with conventional techniques due to their limited sensitivity. This study proposes a novel acoustic-based detection approach that utilizes a distributed elastic variable damping (DEVD) Maxwell model and introduces an A-weighted sound pressure level (SPL) index to enhance detection of small-scale debonding. Comprehensive numerical simulations were integrated with full-scale experiments to analyze acoustic signals under different excitation modes and debonding scenarios. The results show a strong correlation between the A-weighted acoustic metrics and debonding area, and the proposed method reliably distinguishes thin debonding layers that ground-penetrating radar (GPR) could not detect. Our acoustic method demonstrated superior sensitivity to thin-layer debonding, highlighting its potential as a non-destructive tool for early pavement damage detection and improved road maintenance.